A systematic review and meta-analysis assessing adverse event profile and tolerability of nicergoline - Amit Garg; Jun Xu; Mario Fioravanti; Taku Nakashima (BMJ Open)
Objective To evaluate the safety profile of nicergoline compared with placebo and other active agents from published randomised controlled trials.Design Systematic review and meta-analysis of nicergoline compared with placebo and other active agents across various indications.Data sources MEDLINE, Medline-in-process, Cochrane, EMBASE, EMBASE alerts, Cochrane Central Register of Controlled Trials (CENTRAL), Cochrane Database of Systematic Reviews (CDSR) and Cochrane Methodology Register (CMR) for all the randomised controlled trials, open-label or blinded, in adults treated with nicergoline. Studies published until August 2013 were included.Review method 29 studies were included for data extraction. The studies included in this review were majorly from European countries and mostly in cerebrovascular disease (n=15) and dementia (n=8).Results The treatment withdrawals were comparatively lower in the nicergoline group as compared with the placebo group (RR=0.92; 95% CI 0.7 to 1.21) and other active comparators (RR=0.45; 95% CI 0.10 to 1.95), but the difference was non-significant. Incidence of any adverse events (AEs) was slightly higher (RR=1.05; 95% CI 0.93 to 1.2) while incidence of serious AEs was lower (RR=0.85; 95% CI 0.50 to 1.45) in the nicergoline compared with placebo group. Frequency of anxiety was significantly lower in nicergoline as compared with placebo (p=0.01). Other AEs including diarrhoea, gastric upset, dizziness and drowsiness were less frequent in the nicergoline group when compared with placebo/active drugs, but the difference was non-significant. Frequency of hypotension and hot flushes was slightly higher in the nicergoline group but the difference was non-significant. None of the studies reported any incidence of fibrosis or ergotism with nicergoline treatment.Conclusions Nicergoline is an ergot derivative, but its safety profile is better than other ergot derivatives like ergotamine and ergotoxine. This systematic review and meta-analysis suggests that nicergoline has a good safety profile. None of the studies included in this systematic review reported any incidence of fibrosis or ergotism with nicergoline.